Big five and psychological and subjective well-being in Colombian older adults (2019)
The goal of the current study was to investigate the relationships between the Five Factor Model of personality and the dimensions of subjective well-being (positive affect, negative affect, and life satisfaction), and psychological well-being (self-acceptance, personal growth, environmental mastery, autonomy, positive relations with others, and purpose in life). Participants included 618 Colombian adults aged 60–92 years. Multiple linear regression analyses were conducted. Regarding the subjective well-being, neuroticism was associated with lower scores on life satisfaction, and positively associated with negative affect, whereas extroversion and conscientiousness were associated with higher scores on life satisfaction and positive affect. For psychological well-being, neuroticism showed a negative and significant association with all of the psychological well-being dimensions, except purpose in life, whereas extroversion and conscientiousness showed a significant and positive relationship with the six dimensions. Neuroticism, extraversion, and conscientiousness represent personality predispositions for general well-being. Extraversion and conscientiousness are predictors of optimal aging. Neuroticism was the only significant predictor of negative affect.